Sayyidah Khadijah sebagai Role Model Istri dalam Keluarga Islam - Tafuzi Mu’iz, Dzikrul Hakim (LoroNG: Media Pengkajian Sosial Budaya, 2020)
The wife can affect the intensity of a husband’s happiness. However, the husband’s happiness on the attitude and behaviour can suppress polygamy, which frequently occurs. It can also support the realization of a sakinah, mawadah, and warahmah family. The husband’s happiness on the attitude and behaviour can suppress polygamy, which often occurs. It can also support the realization of a sakinah, mawaddah, and warahmah family. As an example of a solid and harmonious household, it can be seen from the relationship of the Prophet’s family with Sayyidah Khadijah. Sayyidah’s behaviour and attitude towards the Prophet reflect how the wife should treat her husband to happiness in the household. This study aims to reveal that Sayyidah Khadijah personally deserves to be a role model for a Salihah wife in an ideal Islamic family concerning QS. Al-Nisa ‘(4): 34. The results of this study are Sayyidah Khadijah has four indicators of Salihah wives in Islam to create an ideal family. First, unite God. Second, be commendable to yourself. Third, be respectable to the husband. And fourth, knowledgeable and have extensive knowledge. These four indicators already exist in the person of Sayyidah Khadijah. All Muslim women can emulate them to become pious wives and create an ideal Islamic family. Istri dapat mempengaruhi intensitas kebahagiaan seorang suami. Kebahagiaan suami atas sikap dan perilaku dari seorang istri diyakini dapat menekan praktek poligami yang kerap kali terjadi. Hal tersebut juga dapat mendukung terwujudnya keluarga sakinah, mawadah dan warahmah. Sebagai teladan rumah tangga yang kokoh dan harmonis, dapat dilihat dari hubungan keluarga Rasulullah dengan Sayyidah Khadijah. Perilaku dan sikap Sayyidah terhadap Rasulullah dapat menjadi cerminan bagaimana perlakuan yang semestinya dilakukan oleh istri kepada suami sehingga suami mendapatkan kebahagiaan dalam rumah tangga tersebut. Penelitian ini bertujuan untuk mengungkapkan bahwasanya pribadi Sayyidah Khadijah layak dijadikan role model istri salihah dalam keluarga Islam yang ideal dengan mengacu pada QS. Al-Nisa’ (4): 34. Hasil dari penelitian ini adalah Sayyidah Khadijah memiliki empat indikator istri salihah dalam islam untuk membuat keluarga yang ideal. Pertama, mengesakan Allah. Kedua, berakhlak terpuji pada diri sendiri. Ketiga, berakhlak terpuji kepada suami. Dan keempat, berilmu dan memiliki pengetahuan yang luas. Keempat indikator ini sudah ada pada pribadi Sayyidah Khadijah dan dapat dicontoh oleh seluruh muslimah sehingga dapat menjadi istri yang salihah dan dapat menciptakan keluarga Islam yang ideal.